DTW-based multi-wavelet data compression algorithm for wireless sensor networks - Si-wang ZHOU; Lan LI (Tongxin xuebao)
A data compression algorithm for wireless sensor networks based on DTW and multi-wavelet transform is pro-posed. Firstly, the correlation and warping path of asynchronous data point pairs is introduced, and then an iterative algo-rithm for solving DTW warping path with maximal similarity is designed. Secondly, a best match point algorithm is pre-sented, which employs prediction to estimate the relationship of synchronous data vectors and then find out the best match points. A sensory data matrix with maximal correlation is thus obtained. Afterwards, a multi-wavelet transform is introduced, which is capable of utilizing the spatial correlation of sensory data matrix and solving the row-column asym-metry problem. Experiment results show that proposed method has higher energy concentration ratio, better reconstruc-tion accuracy and lower running time compared to the traditional distributed wavelet compression algorithm.